National and Ecological Security Contextualized in Nepal’s “Development” Pathways - Rimal, Naresh N. (Journal of APF Command and Staff College, 2018)
The study purports to analysis the environmental security issues in Nepal and its relation with the sustainable national planning. The concerns of ecological security need visible attention at all level from the policy to local. The paper is focused on the need of conceptualizing that there is need of resilience at the level of infrastructural development and maintenance and social capital enhancement and enrichment for a community to be able to withstand a particular event or disaster. Creating a resilient community helps to ensure the kind of development the world is looking for today.